Peran Komisi Pemilihan Umum Kota Palangka Raya dalam Mensosialisasikan Pemilihan Umum Kepala Daerah di IAIN Palangka Raya - Baitul Dawiyah; Dian Endarwati; Diani Kartika Putri; Novita Angraeni (Nusantara Mengabdi Kepada Negeri, 2024)
This research aims to analyze the effectiveness of socialization carried out by the General Election Commission (KPU) of Palangka Raya City in increasing the participation of students from the Palangka Raya State Islamic Institute (IAIN) in the regional head general election. The research methods used were surveys and interviews with related parties. The research results show that the majority of students already know information related to general elections, but there are still several obstacles in understanding voting techniques and the importance of using the right to vote. Based on these findings, this research recommends several strategies that the KPU can implement to increase the effectiveness of outreach, such as involving student organizations, utilizing social media, and holding voting simulation activities.